Trophic ecology of Geoffroy's cat (Leopardus geoffroyi) and mammal prey availability in semi-arid environments of central Patagonia, Argentina - D´Agostino, Romina Laura (2024)
Research on the dietary composition of felids can help improve the perception of rural workersand their tolerance towards this group, which is threatened by human-wildlife conicts. In this context, the purpose of this study was to quantify the diet of Leopardus georoyi in Península Valdés (Patagonia, Argentina) to obtain baseline knowledge of the species dietary habits, trophic ecology, and degree of prey consumption. To this end, 160 fresh scat samples, collected from 2013 to 2016, were analyzed. Ten mammal species, one tinamou bird, one lizard genus, and one insect order were identied. The most frequently consumed prey (63.84%) were small-sized mammals (< 1 kg), accounting for the highest biomass contribution (37.2%). The frequency of each mammal species in the diet was not correlated with their capture frequency (measured through Sherman live traps and pedestrian diurnal transects). This study is the rst to report on the diet of L. georoyi in Argentinean central Patagonia, and it provides information not only on ecological aspects but alsoon the natural history of this felid species.